Evaluasi Program Sistem Pelayanan Rakyat Sidoarjo (SIPRAJA) Di Desa Grabagan - Deva Susanti, Meisy; Sukmana, Hendra (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2025)
The aim of the research is to examine the Evaluation of the Sidoarjo People's Service System Program (SIPRAJA) in Grabagan Village. This research is based on qualitative descriptive data. The types of data obtained include primary and secondary data. Data collection techniques through interviews, observation and field documentation studies. The analysis technique refers to Miles and Huberman (1984), namely collecting, reducing, presenting data and drawing conclusions. The research results show that the Evaluation of the Sidoarjo People's System Program (SIPRAJA) in Grabagan Village was considered successful in optimizing technology for efficiency and effectiveness of services. First, the effectiveness of this program has met the village government's target by providing speed and convenience in population administration services. Second, the efficiency of the SIPRAJA program provides convenience for the community with an efficient service process. Without the need to queue, people can complete administrative matters quickly and without charge. Third, SIPRAJA's ability to offer practical services by providing various types of service features that have been specifically designed to meet the various needs of the community. Fourth, the responsiveness of the SIPRAJA program has succeeded in fulfilling and satisfying the community's need for easy and fast administrative services, especially with the support of the active role of the village government in guiding residents in using SIPRAJA services.